The Influence of Brand Image, Product Innovation and Lifestyle on Purchasing Decisions Purchase of Iphone Smartphones in Patumbak Village, Deli Serdang Village - Wahyu Dwi Sulindra; Sari Wulandari; Suhaila Husna Samosir; Adrial Falahi (International Forum of Researchers and Lecturers, 2026)
This study seeks to examine the influence of brand image, product innovation, and lifestyle on purchasing decisions for iPhone smartphones among residents of Patumbak Village, Dusun V, Deli Serdang. Specifically, it aims to analyze the individual effect of brand image on purchasing decisions, the effect of product innovation on purchasing decisions, and the effect of lifestyle on purchasing decisions, as well as their combined impact. The research employs a descriptive quantitative approach, utilizing questionnaires, interviews, and documentation as data collection techniques. The population consists of 740 residents of Patumbak Village, Dusun V, and the sample of 88 respondents was determined using non-probability sampling with the Slovin formula. The collected data were processed and analyzed through multiple linear regression analysis using SPSS version 26.0. The findings indicate that the calculated F value (205.841) exceeds the F table value (2.71), demonstrating a significant simultaneous effect of brand image, product innovation, and lifestyle on purchasing decisions. Partially, brand image (t = 2.885), product innovation (t = 2.491), and lifestyle (t = 5.570) each show t-values greater than the t table value (1.662), confirming their significant individual influence. Furthermore, the coefficient of determination (R²) of 0.570 reveals that 57% of the variation in purchasing decisions is explained collectively by the three independent variables.